Regional and dynamic specialization of beef production in Mexico (2000-2018) (Agro Productividad, 2022)
Objective: To determine the growth, specialization, and dynamics of beef carcass production in eight regions of Mexico, in the 2000-2018 period.Design/Methodology/Approach: The annual growth rates from 2000 to 2018 in each of the regions were calculated. Based on this information, we were able to determine the relative and dynamic specialization of beef production through Regional Analysis Techniques, such as the Location Quotient and the Differential-Structural Method.Results: During the 2000-2018 period, the domestic beef carcass production had diverse annual growth. Most of the location quotients greater than the unit were obtained in Chiapas and Sonora, while Sinaloa and Chihuahua obtained lower location quotients. The results of the Differential-Structural Method showed that Sinaloa was the most dynamic region, while Veracruz and Sonora have been left behind and showed little specialization in all sub-periods.Limitations/Implications: The differentiated annual growth between regions implied underdevelopment and intra-regional dynamism over time. The change in the productive calling of some regions involved a transformation from being specialized to non-specialized. The dynamics of the regions was determined by hypothetical gains, while the underdevelopment was related to hypothetical losses of various magnitudes.Findings/Conclusions: Sinaloa had the highest growth and dynamism of all the regions. Veracruz and Sonora were left behind and showed little specialization throughout the analyzed period.